Sovereignty And Jurisdiction In Cyberspace - Rahmonova Mohichehra Nodirbek qizi (Genius Journals, 2024)
This article delves into the intricate dynamics of sovereignty and jurisdiction within the realm of cyberspace. With the advent of digital technologies, the traditional concepts of state authority and legal jurisdiction have been challenged by the borderless nature of the internet. The authors explore the definitions of sovereignty and jurisdiction in the context of cyberspace, examining how these concepts extend into the digital domain and the complexities that arise when digital interactions transcend traditional territorial boundaries. Through a thorough literature review, the article provides insights into the evolving landscape of digital governance, drawing from scholarly articles, governmental reports, international treaties, and legal analyses. Additionally, the authors analyze case studies of notable cyber incidents and legal disputes to illustrate how sovereignty and jurisdiction are asserted and contested in practical scenarios. By employing both quantitative data analysis and qualitative assessment of governance mechanisms, including interviews with experts in cybersecurity and international law, the article offers a comprehensive understanding of the challenges and opportunities in regulating cyberspace. Ethical considerations are also addressed, ensuring data privacy, confidentiality, and academic integrity throughout the research process. Overall, this article contributes to the ongoing discourse on sovereignty and jurisdiction in cyberspace, shedding light on the complexities of governing the digital realm in an increasingly interconnected world
Keywords: Sovereignty; Jurisdiction; Cyberspace; Digital Realm